2008
DOI: 10.1016/j.jpain.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Primary Afferent Nociceptors Induced by Intradermal Capsaicin Involves the Peripheral Release of Calcitonin Gene-Related Peptide Driven by Dorsal Root Reflexes

Abstract: Neuropeptides released from axons of primary afferent nociceptive neurons are the key elements for the incidence of neurogenic inflammation and their release is associated with dorsal root reflexes (DRRs). However, whether the release is due to the triggering of DRRs and plays a role in inflammation-induced pain still remain to be determined. The present study assessed the role of calcitonin gene-related peptide (CGRP) in sensitization of primary afferent nociceptors induced by activation of transient receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 65 publications
0
50
0
Order By: Relevance
“…Thermal thresholds (paw withdrawal latency) were detected using a BME-410A thermal dolorimeter (Biomedical Engineering Institute of the Chinese Academy of Medical Sciences), according to the methods described previously (24). Tests were performed at different times (6,8,10,12,14,16,18, and 20 days) following CFA injection. All groups were evaluated 1 day before the injection of CFA in order to determine the baseline mechanical and thermal thresholds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal thresholds (paw withdrawal latency) were detected using a BME-410A thermal dolorimeter (Biomedical Engineering Institute of the Chinese Academy of Medical Sciences), according to the methods described previously (24). Tests were performed at different times (6,8,10,12,14,16,18, and 20 days) following CFA injection. All groups were evaluated 1 day before the injection of CFA in order to determine the baseline mechanical and thermal thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were obtained at baseline (1 day before CFA injection), and day 0 was the time point of CFA injection. Measurements were also obtained on days 6,8,10,12,14,16,18, and 20 following CFA injection.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral sensitisation refers to the shift in response profile of primary, or peripheral, nociceptors, such that they fire more readily (McMahon et al, 2006). Peripheral sensitisation results from the production and release of a swathe of chemical mediators, including those that are released when cells are damaged (Smolin, 1976;Neziri et al, 2012) and those that are released when nociceptors are active (Li et al, 2008). The latter process, called peptidergic or neurogenic inflammation, is triggered by the release of substance P and calcitonin gene related peptide at the peripheral terminals of nociceptors (Li et al, 2008).…”
Section: Reduced Reflex Threshold In People With Painmentioning
confidence: 99%
“…Peripheral sensitisation results from the production and release of a swathe of chemical mediators, including those that are released when cells are damaged (Smolin, 1976;Neziri et al, 2012) and those that are released when nociceptors are active (Li et al, 2008). The latter process, called peptidergic or neurogenic inflammation, is triggered by the release of substance P and calcitonin gene related peptide at the peripheral terminals of nociceptors (Li et al, 2008). Although none of the constituent studies reported the presence or otherwise of peripheral sensitisation, it is reasonable to predict that peripheral sensitisation would have been present in at least some of them -for example, participants with rheumatoid arthritis (Rhudy et al, 2013).…”
Section: Reduced Reflex Threshold In People With Painmentioning
confidence: 99%
“…[57] Substance P has also been found to be upregulated in blood plasma of SCD mice with cold hypersensitivity, [48] and in blood serum from SCD patients. [58] PCR analysis of the DRG from HBSS-BERK and HBAA mice revealed an upregulation of Tachykinin receptor 1 and endothelin 1(ET-1).…”
Section: Potential Mechanisms Of Scd-associated Painmentioning
confidence: 99%